URGENSI PELAYANAN PRIMA DALAM PENINGKATAN MUTU PEMBELAJARAN DI LEMBAGA PENDIDIKAN ISLAM - Yaqien, Nurul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
Every education institution especially Islamic education institution properly provides the best learning services in developing the effort of student quality. Services in education is an absolutely student needs, especially services in developing learning quality, moreover seeing the needs of competitive era. Student’s competence will compete with another competence both in own country and global world particularly in ASEAN region. To undertake the best services in every Islamic education institution, each circle academician of education needs to know the best service concepts. By knowing it that is expected all circle academicians could provide the optimal services for implementing qualified learning. The existence of qualified learning that expected to be able to make excellent generation in all aspects both in religion and general.Keyword: Excellent Service, Quality Improvement, Learning